Crowding the Curriculum? Changes to Grades 9 and 10 Science in British Columbia, 1920-2014 - Sun, Cangjie; Raptis, Helen; Weaver, Andrew (Canadian Journal of Education/Revue canadienne de l'éducation, 2015)
In recent years, educators and academics across North America have argued that science curricula have become increasingly crowded, rendering it almost impossible for teachers to address the multitude of learning outcomes mandated in any given document (e.g., Fortner, 2001; Hacker, 1997). Unfortunately, an analysis of the research literature has failed to substantiate this claim with empirical evidence. This study investigated the claim of crowding in the Science 9 and 10 curricula of one jurisdiction: British Columbia (BC). A content analysis of the Grades 9 and 10 science curricula issued by BC’s government between 1920 to 2014 revealed curricular change characterized by the expansion and reconfiguration of content, persistent attempts to respond to social and educational needs, and constant oscillations between student-centred and subject-centred teaching approaches. This study also illustrates that the potential crowding of the science curriculum suggested by a pattern of constant curricular expansion has as much to do with changing educational theories and ideologies as with scientific developments.